Searching for Enabling and Constraining Arrangements for Better Teaching Practices: EFL Teachers’ Narratives - Isharyanti, Neny; Ragawanti, Debora Tri (Elsya : Journal of English Language Studies, 2023)
Teachers’ teaching practices shape and are shaped by the arrangements in their site of practice. Such arrangements, consisting of the (cultural-discursive) “sayings”, (material-economic) “doings”, and (social-political) “relatings” of the actors involved in and the environment of the practice site, can be defined as “Practice Architectures” (Kemmis, 2019). The practice site that this study focuses on is the teaching practicum activity within a three-month in-service teacher professional education program held jointly by the Indonesian Government and a Higher Education Institution (HEI) (Program Profesi Guru Dalam Jabatan/PPG). Using the framework of Practice Architectures, the study aims to identify the arrangements that occurred and/or were provided by the program in enabling or constraining the program’s standard teaching practicum practices. Through thematic analyses of the teachers’ narratives of their teaching practicum experiences, the results show that these arrangements shaped teachers’ practices in teaching practicum, particularly in the design of the PPG program and the requirements of the assessments. The findings call for the government and HEIs to these arrangements in designing teacher professional development programs, such as the PPG program, to improve future teaching practicum experiences in the program that enable standardised and better teaching practices.